Nanocellulose, a tiny fiber with huge applications. (June 2016) - Abitbol, Tiffany; Rivkin, Amit; Cao, Yifeng; Nevo, Yuval; Abraham, Eldho; Ben-Shalom, Tal; Lapidot, Shaul; Shoseyov, Oded
Graphical abstract: Highlights: Current directions in nanocellulose research. Photonics. Films and foams. Surface functionalization. Nanocomposites. Medicine. Abstract : Nanocellulose is of increasing interest for a range of applications relevant to the fields of material science and biomedical engineering due to its renewable nature, anisotropic shape, excellent mechanical properties, good biocompatibility, tailorable surface chemistry, and interesting optical properties. We discuss the main areas of nanocellulose research: photonics, films and foams, surface modifications, nanocomposites, and medical devices. These tiny nanocellulose fibers have huge potential in many applications, from flexible optoelectronics to scaffolds for tissue regeneration. We hope to impart the readers with some of the excitement that currently surrounds nanocellulose research, which arises from the green nature of the particles, their fascinating physical and chemical properties, and the diversity of applications that can be impacted by this material.